HZSM-5 zeolite cross-linked with ultrathin siliceous layer for intensifying catalytic cracking and diffusion of n-butane. (1st May 2022) - Guan, Linjie; Huang, Chengming; Han, Dingmei; He, Binbin; Zhu, Linhua; He, Dedong; Mei, Yi; Zu, Yun
Graphical abstract: Highlights: HZSM-5 zeolites cross-linked with ultrathin siliceous layer are fabricated. Catalytic cracking performance of n-butane on the silanization zeolites are largely enhanced. Diffusion properties of n-butane on the zeolites are quantified by in situ FTIR spectroscopy. Correlation between n-butane conversion rate per Brønsted acid site and diffusivity is negative. HZSM-5 with siliceous monolayer intensifies catalytic performance and diffusivity of n-butane. Abstract: A series of HZSM-5 zeolites are fabricated to make it cross-link with an external ultrathin siliceous layer by chemical liquid deposition and the corresponding thickness is measured by TEM and XPS analysis. In situ FTIR experiments disclose that the external surface acidic sites of HZSM-5 zeolite can be covered even by siliceous monolayer (0.7 ∼ 1.3 nm, HZ5-S1). In comparison to parent HZSM-5, the catalytic cracking performance of n-butane over the modified zeolites are evidently enhanced. In particular, the n-butane conversion rate per Brønsted acid site over the HZ5-S2 (16.02 min −1 ) at 550 °C is 2.82 times than that over the HZSM-5 (5.68 min −1 ). Meanwhile, the diffusion properties of n-butane over the zeolites are quantified by in situ FTIR spectroscopic analysis. Negative correlation between steady-state diffusivity and n-butane conversion rate per Brønsted acid site can be found, which unravels the origin of the progressive decrease in the catalytic stability. Under comparable conditions, more advantages can be greatly achieved by HZ5-S1 catalyst in the catalytic activity and the yields to light olefins due to the benign diffusivity and the elimination of external surface acidic sites. This study can provide a guidance for the understanding of diffusion intensification and the rational design of superior catalyst for the catalytic cracking reactions of alkanes.